(untitled) (Balkan Journal of Applied Mathematics and Informatics, 2022)
The aim of this paper is to obtain the general solution of a reciprocal functional equation of the form equation*1f(x+u,y+v)=12f(2x+y,2u+v)+12f(y,v)equation* and investigate its generalized Hyers-Ulam stability.